Pembuatan Teh Antioksidan dari Beberapa Tanaman Pekarangan pada Kelompok Pemberdayaan Kesejahteraan Keluarga Komplek Permata Hijau Banjarbaru Kalimantan Selatan - Kissinger Kissinger; Rina Muhayah Noor Pitri (Magister of Forestry,Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
The Permata Hijau Banjarbaru Family Welfare Empowerment Group is an activity partner who carries out various activities in their daily life. Consuming foods that contain high antioxidants is very important in the midst of the COVID-19 pandemic. The use of natural materials found around our environment is asolution for improving the health of the community, one of which is plants that have antioxidant capacity. Partners do not have the knowledge and technology about antioxidant plants and their proper and targeted utilization methods. The purpose of the service was to train PKK members in making antioxidanttea by utilizing yard plant materials. The solutions offered in answering partner problems were through 4 stages, namely: preparation stage, science and technology transfer stage in the form of discussion, demonstration stage, and evaluation stage. 83.33% of PKK members who became the target audience understood the socialization material about antioxidant tea made from yard plants. A total of 10 people understood the socialization material from the initial target of 4 people. Capability of tea-making skills, serving dosage and packaging were obtained by 8 people who mastered the skills well. Overall service activities were categorized as successful in transferring knowledge and technology to the target audience. The use of yard plants as ingredients for making antioxidant tea was well received by partnersKey words: antioxidant, yard, plant, tea